From polar night to midnight sun: Diel vertical migration, metabolism and biogeochemical role of zooplankton in a high Arctic fjord (Kongsfjorden, Svalbard) - Darnis, Gérald; Hobbs, Laura; Geoffroy, Maxime; Grenvald, Julie Cornelius; Renaud, Paul; Berge, Jørgen; Cottier, Finlo Robert; Kristiansen, Svein; Daase, Malin; Søreide, Janne; Wold, Anette; Morata, Nathalie; et al. (Limnology and Oceanography, 2017)
Source at http://dx.doi.org/10.1002/lno.10519 Zooplankton vertical migration enhances the efficiency of the ocean biological pump by translocating carbon (C) and nitrogen (N) below the mixed layer through respiration and excretion at depth. We measured C and N active transport due to diel vertical migration (DVM) in a Svalbard fjord at 79°N. Multifrequency analysis of backscatter data from an Acoustic Zooplankton Fish Profiler moored from January to September 2014, combined with plankton net data, showed that Thysanoessa spp. euphausiids made up > 90% of the diel migrant biomass. Classical synchronous DVM occurred before and after the phytoplankton bloom, leading to a mismatch with intensive primary production during the midnight sun. Zooplankton DVM resulted in C respiration of 0.9 g m−2 and ammonium excretion of 0.18 g N m−2 below 82 m depth between February and April, and 0.2 g C m−2 and 0.04 g N m−2 from 11 August to 9 September, representing > 25% and > 33% of sinking flux of particulate organic carbon and nitrogen, respectively. Such contribution of DVM active transport to the biological pump in this high-Arctic location is consistent with previous measurements in several equatorial to subarctic oceanic systems of the World Ocean. Climate warming is expected to result in tighter coupling between DVM and bloom periods, stronger stratification of the Barents Sea, and northward advection of boreal euphausiids. This may increase the role of DVM in the functioning of the biological pump on the Atlantic side of the Arctic Ocean, particularly where euphausiids are or will be prevalent in the zooplankton community.